Access to reeds and mat making in the lower Volta basin of Ghana - Ayivor, J.S (Singapore Journal of Tropical Geography. Wiley Publishing Asia Pty Ltd. 35 (2014) 197–212. doi:10.1111/sjtg.12068., 2014)
This paper explores the origins of pressures on reeds and sedges used for mat making in the lower Volta basin of Ghana, and their impact on the socially embedded system which dictates access to reed fields. Data for the study were collected through field work employing participatory rural appraisal methods in 18 communities, involving 152 mat weavers. The findings showed that the mat-weaving industry has contributed immensely in providing poor women a means of livelihood but reed marshes in the basin have reduced in recent years due to hydrological changes in the area caused by the damming of the Volta upstream. The decline in the availability of reed is exerting immense pressure on this once freely available resource, thus inducing landlords to impose a price on the rights of entry into marshlands by reed collectors. The imposition of these charges affected the very people that the mat-weaving industry is targeted to help. The study recommends the local and central government to play a more active role and civil society groups to broaden the livelihood base of women living in this region.
Keywords: access; reeds and sedges; mat weaving; tenure security; livelihoods; Ghana